ANALYSIS OF DIGITAL LITERACY IN THE USE OF THE INTERNET IN STUDENTS - Nurullah Sururi Afif; Putie Maharani Basa; Anantha Zakharia (Jurnal Scientia, 2023)
This study aims to examine the level of understanding of digital literacy in the use of the internet by students. Indonesian students' level of understanding of digital literacy can vary depending on their level of education, interests, and experience. Increased awareness about the importance of digital literacy among students, especially due to the increasingly dominant role of technology and the internet in everyday life. Some Indonesian students have a good understanding of digital literacy and are able to use technology carefully and effectively. They have basic skills such as operating digital devices, accessing information online, and communicating through social media. They may also have an understanding of digital security, online privacy, and how to validate the authenticity of information they encounter on the internet. However, there are still some students who may have a limited understanding of digital literacy. Some of the factors influencing this understanding are limited access to technology, lack of formal training or education in terms of digital literacy, and lack of awareness about the potential risks and dangers associated with the use of technology. This study sample used was as many as 72 people. Based on the results of the analysis, it can be concluded that students have excellent digital literacy in internet use.